Ambivalensi Pemikiran Mahmud Syaltut tentang Fikih Perempuan - Mahmud Arif (Al-Manahij: Jurnal Kajian Hukum Islam, 2011)
In general, we know about Egypt very well, because of all this time, Egypt, especially Kairo, has been viewed as one of the centers of Islamic thought in the world. Naturally this country had a lot of Islamic thinkers, like Mahmud Syaltut (d. 1963) that has become the Rector of al-Azhar University. The influence of his thought overstepped the bounds of time and political territory. The Islamic jurisprudence is an inseparable legal thought from the fulfillment of social demands. One of the evidences is itsâ€™ response to actual issues, like gender equality represented in his opinions about domestical duty, women testimony, girl marriage, and poligamy. As a thinker in the Islamic jurisprudence, Syaltut has endeavored to respond such issues, including gender. As a reformer in the turbulent time, his reflection on such matters expressed critical preference, so frequently looked different from the prevalent opinion. In one side, his reflection was â€œliberalâ€ because of his bravery in stepping beyond the Islamic orthodoxy and the modernity, but in another side, his thought was â€œconservativeâ€if it was viewed from his endorsement to the old Islamic thought that reflected a gender bias. This showed the uniqueness and the ambivalence of his thought, so very interesting to being studied.